Análise adaptativa por regeneração da malha - Portela, Julio Cesar da Silva (1991)
This work is concerned with the development of an adaptive remeshing scheme for the h-version of de Finite Element Method, applied to plane elasticity and plate bending problems. The advancing front technique is employed for mesh generation. A linear triangular finite element is used and a-posteriori error estimator is based on projections and smoothing tecniques. Several problems are analysed and results compared with the analytical solutions. Numerical rates of convergence are also investigated.